Taxogenomic status of phylogenetically distant Frankia clusters warrants their elevation to the rank of genus: A description of Protofrankia gen. nov., Parafrankia gen. nov., and Pseudofrankia gen. nov. as three novel genera within the family Frankiaceae - Gtari, Maher (Frontiers in Microbiology, 2022)
The genus Frankia is at present the sole genus in the family Frankiaceae and encompasses filamentous, sporangia-forming actinomycetes principally isolated from root nodules of taxonomically disparate dicotyledonous hosts named actinorhizal plants. Multiple independent phylogenetic analyses agree with the division of the genus Frankia into four well-supported clusters. Within these clusters, Frankia strains are well defined based on host infectivity range, mode of infection, morphology and their behaviour in culture. In this study, phylogenomics, overall genome related indices, together with available data sets for phenotypic and host plant range available for the type strains of Frankia species, were considered. The robustness and the deep radiation observed in Frankia at the subgeneric level, fulfilling the primary principle of phylogenetic systematics, was strengthened by establishing genome criteria for new genus demarcation boundaries. Therefore, the taxonomic elevation of the Frankia clusters to rank of genus is proposed. The genus Frankia should be revised to encompass cluster 1 species only and three novel genera, Protofrankia gen. nov., Parafrankia gen. nov. and Pseudofrankia gen. nov., are proposed to accommodate cluster 2, 3 and 4 species respectively. New combinations for validly named species are also provided.